Ecuador : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic developments in Ecuador during the 1990s. Inflation fell from an average of about 50 percent in 1988-92 to 22 percent in April 1995. Economic activity rebounded, and international reserves were rebuilt. Relations with foreign creditors were normalized through an 'exit' Paris Club rescheduling in mid-1994 and the completion of a debt- and debt-service-reduction operation with external commercial creditors in early 1995 that was expected to facilitate the return to external viability.